(untitled) (De Rebus Antiquis, 2020)
In this article I want to show the negotiations of the Emperor Julian about recruitment and Anonna Militaris. I’m trying to develop some ideas on Julian’s Military History during his time as a Cesar of Constantius II and as an Emperor. We are joying some arguments to understand his preparation for the military life.